Pengembangan Bahan Ajar Psikologi Pendidikan pada Program Studi Pendidikan Guru Madrasah Ibtidaiyah Pascasarjana IAIN Kudus - Muzdalifah, Muzdalifah; Yuliatun, Yuliatun; Rois, Taufikul Lutfi (Pascasarjana IAIN Kudus, 2022)
The Development of Educational Psychology Teaching Materials in the Postgraduate Program of Madrasah Ibtidaiyah Teacher Education of IAIN Kudus. This research is motivated by various facts, First, Educational Psychology is a compulsory subject in the PGMI IAIN Kudus Masters Study Program; Second, so far very few lecturers at IAIN Kudus have written teaching materials; Third, students need learning resources, especially in Educational Psychology courses; Fourth, the characteristics of the courses are still not in accordance with the characteristics and needs of students. The purpose of this study was to determine the feasibility of educational psychology book teaching materials in the IAIN Kudus Postgraduate Madrasah Ibtidaiyah Teacher Education Study Program. This research is a developmental research that refers to the 4-D model according to Thiagarajan, Semmel and Semmel. However, this research is limited to three stages, namely 1) the define stage, 2) the design stage, and the develop stage. The feasibility of windowed book teaching materials is viewed from 4 aspects, namely content feasibility, presentation feasibility, and language feasibility. The results of this study indicate that the developed educational psychology books are suitable for use as teaching materials. Penelitian ini dilatarbelakangi oleh berbagai fakta, Pertama, Psikologi Pendidikan merupakan mata kuliah wajib di Program Studi S2 PGMI IAIN Kudus; Kedua, selama ini sedikit sekali dosen IAIN Kudus yang menulis bahan ajar; Ketiga, Mahasiswa memerlukan sumber belajar khususnya pada mata kuliah Psikologi Pendidikan; Keempat, karakteristik mata kuliah masih sangat kurang sesuai dengan karakteristik dan kebutuhan mahasiswa. Tujuan dari penelitian ini untuk mengetahui kelayakan bahan ajar buku Psikologi Pendidikan di Program studi Pendidikan Guru Madrasah Ibtidaiyah Pascasarjana IAIN Kudus Penelitian ini merupakan penelitian pengembangan yang mengacu pada model 4-D menurut Thiagarajan, Semmel dan Semmel. Namun, penelitian ini dibatasi pada tiga tahap yaitu 1) tahap pendefinisian (define), 2) tahap perancangan (design), dan tahap pengembangan (develop). Kelayakan bahan ajar buku berjendela ditinjau dari 4 aspek yaitu kelayakan isi, kelayakan penyajian, dan kelayakan bahasa. Hasil penelitian ini menunjukkan bahwa buku Psikologi pendidikan yang dikembangkan layak digunakan sebagai bahan ajar.